Historical perspectives on cadmium toxicology - Nordberg, Gunnar F. (Toxicology and applied pharmacology, 2009)
The first health effects of cadmium (Cd) were reported already in 1858. Respiratory and gastrointestinal symptoms occurred among persons using Cd-containing polishing agent. The first experimental toxicological studies are from 1919. Bone effects and proteinuria in humans were reported in the 1940's. After World War II, a bone disease with fractures and severe pain, the itai-itai disease, a form of Cd-induced renal osteomalacia, was identified in Japan. Subsequently, the toxicokinetics and toxicodynamics of Cd were described including its binding to the protein metallothionein. International warnings of health risks from Cd-pollution were issued in the 1970's. Reproductive and carcinogenic effects were studied at an early stage, but a quantitative assessment of these effects in humans is still subject to considerable uncertainty. The World Health Organization in its International Program on Chemical Safety, WHO/IPCS (1992) (Cadmium. Environmental Health Criteria Document 134, IPCS. WHO, Geneva, 1–280.) identified renal dysfunction as the critical effect and a crude quantitative evaluation was presented. In the 1990's and 2000 several epidemiological studies have reported adverse health effects, sometimes at low environmental exposures to Cd, in population groups in Japan, China, Europe and USA (reviewed in other contributions to the present volume). The early identification of an important role of metallothionein in cadmium toxicology formed the basis for recent studies using biomarkers of susceptibility to development of Cd-related renal dysfunction such as gene expression of metallothionein in peripheral lymphocytes and autoantibodies against metallothionein in blood plasma. Findings in these studies indicate that very low exposure levels to cadmium may give rise to renal dysfunction among sensitive subgroups of human populations such as persons with diabetes.